Romania : Financial Sector Assessment Program-Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses findings of the Detailed Assessment of Observance of the Basel Core Principles (BCP) for Effective Banking Supervision in Romania. The supervisory approach of the National Bank of Romania (NBR) has been changing toward a more risk based approach since the previous BCP assessment, but more needs to be done. Further development of the NBR's supervisory approach will make supervision more effective and in line with the requirements of the 2012 BCP. The NBR may need to devote more supervisory attention to banks' risk models and building up further expertise in specialized areas such as information technology and market risk. In the area of corrective actions and sanctions, the NBR should review its framework to ensure it is protected from undue legal challenges.